(untitled) (Research, Society and Development, 2022)
Obesity is characterized by an excess of body fat, which can cause damage to health. Its etiology is multifactorial, resulting from the interaction between genetic, socioeconomic, environmental, and psychological aspects. The objective of this study is to sensitize students between the seventh year of elementary school and the third year of high school in two schools in the state of Sergipe about the health damage that obesity and eating disorders can bring to adolescents. As a methodology, educational actions and conversation circles were carried out to explain how these diseases can affect quality of life. As a result and discussion, a total of 260 students were attended, from the morning and afternoon shifts, within the age group from 12 to 19 years old. This work made it possible to show how direct communication with the young public allows the exchange of experiences and knowledge by both parts, and can prevent serious damage to the health of this public, related to obesity and eating disorders.